Single electron emission in two-phase xenon with application to the detection of coherent neutrino-nucleus scattering - Santos,E; Edwards,B; Chepel,V; Araújo,HM; Akimov,DY; Barnes,EJ; Belov,VA; Burenkov,AA; Currie,A; Deviveiros,L; Ghag,C; Hollingsworth,A; et al. (The Journal of High Energy Physics, 2011)
We present an experimental study of single electron emission in ZEPLIN-III, a two-phase xenon experiment built to search for dark matter WIMPs, and discuss appli-cations enabled by the excellent signal-to-noise ratio achieved in detecting this signature. Firstly, we demonstrate a practical method for precise measurement of the free electron lifetime in liquid xenon during normal operation of these detectors. Then, using a realistic detector response model and backgrounds, we assess the feasibility of deploying such an instrument for measuring coherent neutrino-nucleus elastic scattering using the ionisation channel in the few-electron regime. We conclude that it should be possible to measure this elusive neutrino signature above an ionisation threshold of ~3 electrons both at a stopped pion source and at a nuclear reactor. Detectable signal rates are larger in the reactor case, but the triggered measurement and harder recoil energy spectrum afforded by the accelerator source enable lower overall background and fiducialisation of the active volume.